GREEN ACCOUNTING AND GREEN INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE MODERATED WITH GOOD CORPORATE GOVERNANCE - Ni Komang Pusparini; I Ketut Sujana (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Financial performance shows how well a company manages its resources to achieve its goals. In the context of sustainability, companies in the transportation and logistics sector for the period 2021–2024, as high contributors to carbon emissions, are faced with demands to implement environmentally friendly practices. This study aims to examine the influence of green accounting and green intellectual capital (GIC) on financial performance, as well as the role of good corporate governance (GCG) as a moderating variable. The research sample consists of 24 companies in the transportation and logistics sector listed on the Indonesia Stock Exchange for the period 2021–2024, selected using purposive sampling. The data were analyzed using moderated regression analysis (MRA), and the selection of GCG indicators used confirmatory factor analysis (CFA). The results show that green accounting and GIC support improved financial performance, but GCG does not strengthen this relationship. This study suggests improving the quality of GCG to be in line with the company's sustainability commitments.